Post-late Cretaceous paleomagnetic rotations of the Pontides, Northern Anatolia, Türkiye - Ucar, Hakan; Cengiz, Mualla (International journal of earth sciences : Geologische Rundschau, 2024)
Northern Anatolia has been the subject of many studies due to its complex tectonic structure. Here we report on a paleomagnetic study sampled from upper Cretaceous to middle Miocene sedimentary and volcanic rocks at 54 sites running along the traces of the North Anatolian Fault in the Pontides, Northern Türkiye, to define the post-late Cretaceous tectonic evolution of the area. The results were evaluated together with previously published paleomagnetic data around the Kırşehir Block and the Pontides. The rotational pattern showed distinct phases in the Pontides after the late Cretaceous. A predominant late Cretaceous-middle Eocene clockwise rotation up to 38.1° ± 17.4° probably occurred due to the progressive collision between the Pontides and the Kırşehir Block from west to east. The ongoing deformation continued along the İzmir-Ankara-Erzincan Suture Belt during the middle Eocene-middle Miocene time as evidenced by the paleomagnetic rotation pattern, while no significant rotations were observed further north of the suture zone at this time period. On the other hand, middle Miocene paleomagnetic sites showed a counterclockwise rotation, reflecting the westward escape of the Anatolian microplate, while local fault-bounded vertical block rotations were apparent in places. Graphical Abstract